Nuclear localization of alpha-synuclein affects the cognitive and motor behavior of mice by inducing DNA damage and abnormal cell cycle of hippocampal neurons - Pan, Yue; Zong, Qinglan; Li, Guoxiang; Wu, Zhengcun; Du, Tingfu; Huang, Zhangqiong; Zhang, Ying; Ma, Kaili (Frontiers in Molecular Neuroscience, 2022)
Nuclear accumulation of alpha-synuclein (α-syn) in neurons can promote neurotoxicity, which is considered the key factor in the pathogenesis of synucleinopathy. The damage to hippocampus neurons driven by α-syn pathology is also the potential cause of memory impairment in Parkinson’s disease (PD) patients. In this study, we examined the role of α-syn nuclear translocation in the cognition and motor ability of mice by overexpressing α-syn in cell nuclei in the hippocampus. The results showed that the overexpression of α-syn in nuclei was able to cause significant pathological accumulation of α-syn in the hippocampus, and quickly lead to memory and motor impairments in mice. It might be that nuclear overexpression of α-syn may cause DNA damage of hippocampal neurons, thereby leading to activation and abnormal blocking of cell cycle, and further inducing apoptosis of hippocampal neurons and inflammatory reaction. Meanwhile, the inflammatory reaction further aggravated DNA damage and formed a vicious circle. Therefore, the excessive nuclear translocation of α-syn in hippocampal neurons may be one of the main reasons for cognitive decline in mice.